The Islamic Injunction on Hijab: The Practice and The Dynamics of The Agitation for The Adoption of The Use of Hijab in The State - Mufutau Olusola Bello (AJIS: Academic Journal of Islamic Studies, 2020)
Ekiti State is one of the States in the South Western part of Nigeria. The dominant religions in the State are Christianity and Islam. Like other parts of the world, there is a strong wave of Islamic revivalism by the Muslims while the Christians are not relenting in their evangelism to draw more people to their fold. One of the expressions of the revivalism by the Muslims is the voluntary adoption of the hijāb by many female Muslims. Consequently, the average female Muslim is a Mājubah of one sort or the other. The state is now faced with teeming number of women who wants to use the hijāb in the Western based schools and the government official work places. Many of them are now faced with either to remove the hijāb because of education or to look for a white collar job in the State while others who want to strictly hold to their faith were making agitations for the use of the hijāb. The paper looks at the concept of hijāb in Islam, the mode of dressing in Ekiti State, its compatibility and the differences with the traditional dressing in the State and the dynamics of the agitation for the adoption of the use of hijāb. The work made use of both primary and secondary sources. Islamic literature, archival materials and pamphlets were consulted while interviews were made with relevant personalities in the state. The result revealed a good approach adopted by the government of Ekiti State in taking care of the agitations of the Muslims on the use of hijab in government official places of work and students in formal public schools. The Ekiti model is therefore suggested to be adapted and adopted by other states in Nigeria where the problem of hijab have snowballed into crises